Connective tissue dysplasia in patients with mitral valve prolapse. - M. A. Kuznetsova (Medičnì Perspektivi, 2013)
Recently displasia of connective tissue is much spoken and written about. As a rule, these are scientific articles and reviews in which difficult terms prevail and doctors don't read them up to the end. And the problem, meanwhile, exists, and problem is very interesting. It is known that connective tissue consists of cells, fibers and intercellular substance. It is well known that it may be dense and loose and is widespread throughout the organism – skin, bones, cartilagle, vessels wall, stroma of bodies and even blood – at the basis of every element is connective tissue. The structure of connective tissue is well studied, and all biochemical structures are identified. Successes of molecular genetics allowed to define types, structure and localization of the genes which are responsible for synthesis of various elements. First of all we are interested in fibers of connective tissue – collagen with main function to maintain form, and the elastin, providing ability to reduction and relaxation. Dysplasia of connective tissue – the process genetically determined, i.e. at the basis of everything is mutations of the genes which are responsible for synthesis of fibers. Mutations may be the most various and in the most different genes. As a result of mutations collagen chains are formed incorrectly. Thus, they are shorter (deletion), or longer (insertion), they join not that amino acid (a dot mutation). So-called abnormal trimers of collagen appear, they don't maintain due mechanical loadings. The same is with elastin. The clinical picture will be defined by quantity and quality of mutations. Unfortunately, not only specific appearance and cosmetic defects belong to manifestations of dysplasia of connective tissue, but also heavy pathological changes of internal organs and the musculoskeletal apparatus.